All-solid-state batteries and their remaining challenges - Kasemchainan, J; Bruce, P (Johnson Matthey, 2018)
All-solid-state batteries, which utilise a solid electrolyte in place of liquid electrolytes, have the potential for higher energy densities and greater safety than current lithium-ion batteries. However they still face many challenges before the technology is ready to be commercialised. This short report summarises the current state of knowledge in all-solid-state batteries including the electrical, electrochemical and mechanical properties of the electrolytes, and the challenges that remain to be overcome in their development and processing.